Idea integralności w rozwoju człowieka dorosłego = The idea of integrity in adults development - Mróz, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Psychological theories that represent the model of multidimentional developmental changes offer a complicated approach to the problem of integrity in adults development. Integrity is defined as the coherence of functioning of different elements of mental structure. However, it must be differentiated from developmental synchrony. Integrity implies unity of the structure working as a system.
Keywords: rozwój człowieka; integralność rozwojowa; zdrowie psychiczne; wielokierunkowe zmiany rozwojowe; human development; developmental integrity; mental health; multidimensional developmental changes